CABLE SYSTEMS ADMINISTRATION AND MANAGEMENT SERVICES (SISKAMAYA) IN PT. TELKOM - Agus Wahyudin; Aqwam Rosadi Kardian,S.kom.,MMSI (Jurnal Sistem Informasi, 1998)
The main purpose of SISKAMAYA made is to increase service to customers and prospective customers. ADKAB subsystem data was still not in accordance with field data. Toll Claim subsystem implemented needs to be improved performance manually using computer assistance. To connect the distance between front room with the far back room, then the data processing method selected is the On-line systems.